A STUDY FOR LINGUAL NERVE PROTECTION DURING EXTRACTION OF THIRD MOLAR USING LINGUAL REACTOR - 2Singh Saurabh*1, Verma Neeraj (Journal of Biomedical and Pharmaceutical Research, 2017)
Lingual nerve damage during surgical removal of third molar is most common nerve damage reported. Its incidence rate has been reported from 0.6 to as high as 22% in various studies conducted. Our aim was to study the effect of broad retractor for protection of lingual nerve during surgical removal of third molar. In a study of eighty patients who went for surgical extraction buccal and lingual flap was raised keeping lingual bone intact, buccal ostoetomy was done in all cases and broad lingual retractor was used to for lingual flap retraction then the incidence of lingual nerve damage noted. During this study we observed that incidence rate of lingual nerve damage was 5%.Sometimes it necessary to reflect lingual flap as in cases of distoangular and horizontal impactions for better visualization lingual nerve damage can be minimized with proper adaptation of broad shaped lingual retractor.